The role of maternal stress during pregnancy, maternal discipline, and child COMT Val158Met genotype in the development of compliance. Issue 5 (21st May 2012) - Kok, Rianne; Bakermans‐Kranenburg, Marian J.; van IJzendoorn, Marinus H.; Velders, Fleur P.; Linting, Mariëlle; Jaddoe, Vincent W.V.; Hofman, Albert; Verhulst, Frank C.; Tiemeier, Henning
Abstract Maternal discipline is an important predictor of child committed compliance. Maternal stress can affect both parenting and child development. In a large population‐based cohort study (N = 613) we examined whether maternal discipline mediated the association between maternal stress during pregnancy and child compliance, and whether COMT or DRD4 polymorphisms moderated the association between maternal discipline and child compliance. Family‐related and general stress were measured through maternal self‐report and genetic material was collected through cord blood sampling at birth. Mother–child dyads were observed at 36 months in disciplinary tasks in which the child was not allowed to touch attractive toys. Maternal discipline and child compliance were observed in two different tasks and independently coded. The association between family stress during pregnancy and child committed compliance was mediated by maternal positive discipline. Children with more COMT Met alleles seemed more susceptible to maternal positive discipline than children with more COMT Val alleles. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 451–464, 2013